2017
DOI: 10.1016/j.jes.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Monohalogenated acetamide-induced cellular stress and genotoxicity are related to electrophilic softness and thiol/thiolate reactivity

Abstract: Haloacetamides (HAMs) are cytotoxic, genotoxic, and mutagenic byproducts of drinking water disinfection. They are soft electrophilic compounds that form covalent bonds with the free thiol/thiolate in cysteine residues through an SN2 reaction mechanism. Toxicity of the monohalogenated HAMs (iodoacetamide, IAM; bromoacetamide, BAM; or chloroacetamide, CAM) varied depending on the halogen substituent. The aim of this research was to investigate how the halogen atom affects the reactivity and toxicological propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…For the three haloamides tested, PELI max could be predicted by ATS3p (an autocorrelation descriptor of centered Broto-Moreau autocorrelation weighted by polarizabilities) with R 2 = 0.9345 (P=0.1645), and PELI1.5 could be predicted by G (Gibbs free energy) with R 2 = 0.9943 (P= 0.0482). The correlation of E lomo to toxicity of haloacetic acids is consistent with other published studies 4,16,25,67 The QSAR modeling exercise of the DBPs suggested that chemical properties of the molecules, for example, topological and quantum chemical properties, correlate with the genotoxicity of DBPs. In addition, the correlation of different descriptors implicated different mechanism(s).…”
Section: Qsar Physicochemical Descriptors Versus Genotoxicity To Assess Mechanismssupporting
confidence: 89%
See 1 more Smart Citation
“…For the three haloamides tested, PELI max could be predicted by ATS3p (an autocorrelation descriptor of centered Broto-Moreau autocorrelation weighted by polarizabilities) with R 2 = 0.9345 (P=0.1645), and PELI1.5 could be predicted by G (Gibbs free energy) with R 2 = 0.9943 (P= 0.0482). The correlation of E lomo to toxicity of haloacetic acids is consistent with other published studies 4,16,25,67 The QSAR modeling exercise of the DBPs suggested that chemical properties of the molecules, for example, topological and quantum chemical properties, correlate with the genotoxicity of DBPs. In addition, the correlation of different descriptors implicated different mechanism(s).…”
Section: Qsar Physicochemical Descriptors Versus Genotoxicity To Assess Mechanismssupporting
confidence: 89%
“…3,13 Genotoxicity mechanisms of DBPs are also strongly related to their structures. For example, for halogenated DBPs, oxidative stress-induced DNA damage [14][15][16][17][18][19][20][21] and DNA alkylation [22][23][24][25] are two major mechanisms. Halonitriles may also induce genomic damage by cell cycle disruption and the induction of hyperploidy.…”
Section: Introductionmentioning
confidence: 99%
“…The ROS generation by xenobiotics may pose oxidative damage to essential biomolecules and cause functional deficits of cells, which may lead to cell death and even some adverse outcomes such as cancer with the absence of compensatory mechanisms. 47,48 The oxidative stress has been reported to relate to the genotoxicity and mutagenicity induced by mono-HAAs through inhibiting glycolysis by ROS. 47,78 Halophenols have been reported to generate phenoxy radical intermediates and halobenzoquinones during metabolism, and halobenzoquinones can induce ROS production in cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2016), including the subsequent generation of ROS (Pals et al. 2013, 2017). Based on concurrent up-regulation of nuclear factor kappa B (Nf- k B) and mitogen-activated protein kinase (MAPK) pathways, we speculate that this could involve downstream activation of Toll-like receptors (TLRs) (van der Veen et al.…”
Section: Discussionmentioning
confidence: 99%